Breakout Rooms Serve as a Suitable Tool for Interprofessional Pre-Service Online Training among Students within Health, Social, and Education Study Programs - Kari Almendingen; Torhild Skotheim; Ellen Merethe Magnus (MDPI AG, 2022)
Higher education institutions must prepare students from health, social, and teacher education programs for interprofessional collaboration (IPC) among children and young people with challenging childhood experiences. We wanted to explore if digital small group rooms, breakout rooms, are feasible for students to learn about, from, and with each other in an interprofessional learning (IPL) initiative, in order to practice IPC. This study is a repeated cross-sectional study from the academic years 2020/21 and 2021/22 with 5412 students. The students worked in student-led IPL groups with a case-based learning approach and limited interaction with supervisors. The youngest students agreed to a larger extent that they learned more about, from, and with other students. The teacher students were more positive towards discussing sensitive issues in breakout rooms than the health students. The health students agreed to a larger extent than the teacher students that breakout rooms were suited for pre-service IPC training. The results from this study indicate that breakout rooms provide a potential arena to practice generic skills. If properly organized and structured, breakout rooms can be an excellent learning resource. Breakout rooms provide a safe online environment for learning and practicing IPC, and for training on talking about sensitive issues.